SHAKESPEARE'S ENDURING LEGACY: A TIMELESS JOURNEY INTO LITERATURE - Xayrullayeva Sevara Bobirovna; Tohirova Umida Akramovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: William Shakespeare, often regarded as the greatest playwright in the English language, continues to captivate readers and audiences centuries after his time. His legacy extends beyond the confines of a historical figure; it is an indelible mark on the world of literature and drama. In this exploration of Shakespeare's life, works, and lasting influence, we delve into the timeless genius that is the Bard of Avon. We know that all works published today are not read enough by the youth and the society. Compared to modern works, the value of ancient works is high. Especially the immortal works of writers like Shakespeare are still read today. What is the reason for this? Through this article, we will compare Shakespeare's works, his importance, his place in society and the difference from modern works.